Antiviral efficacy of bromo-anilino substituents of 4, 5-dihydrofuran-3-carboxylate compound CW-33 against Japanese encephalitis virus. Issue 23 (1st December 2019) - Lien, Jin-Cherng; Lin, Chen-Sheng; Lai, Hsueh-Chou; Tsai, Yu-Chi; Lin, Yu-Fong; Huang, An-Cheng; Huang, Su-Hua; Lin, Cheng-Wen
Graphical abstract: Highlights: A bromo substitution (CW-33K) on at the C-2 anilino ring of CW-33 improved the antiviral activity JEV. CW-33K exhibited the highest antiviral efficacy, which IC50 value was less than 5 μM. CW-33K significantly inhibited the JEV replication at the early and late stages. Abstract: Japanese encephalitis virus (JEV), a mosquito-borne flavivirus, occasionally causes severe central nervous system disorders in the risk zone where more than 3 billion people reside. Our prior studies demonstrated antiviral potential of 4, 5-dihydrofuran-3-carboxylate compound CW-33 (ethyl 2-(3′, 5′-dimethylanilino)-4-oxo-4, 5-dihydrofuran-3-carboxylate) and its derivative CW-33A ((ethyl 2-(2-fluoroanilino)-4-oxo-4, 5-dihydrofuran-3-carboxylate) against JEV infection ((Int. J. Mol. Sci. 2016, 17: E1386; Sci. Rep. 2018, 8: 16595). This study synthesized six new CW-33 derivatives containing chloro, or bromo groups at the C-2, C-3, or C-4 of anilino ring of CW-33, and assessed the antiviral activity and mechanisms of these chloro- and bromo-anilino substituted derivatives. CW-33K, CW-33L and CW-33M had the bromo-substituents at the C-2, C-3, or C-4 of anilino ring of CW-33, respectively, showing the higher anti-JEV activity than CW-33 and other derivatives. CW-33K (ethyl 2-(2-bromoanilino)-4-oxo-4, 5-dihydrofuran-3-carboxylate) exhibited the highest antiviral efficacy and therapeutic index. The IC50 value of CW-33K was less than 5 μM for reducing JEV-induced cytopathic effect, virus infectivity and virus yield. CW-33K significantly inhibited the JEV replication at the early and late stages, suppressing viral RNA synthesis and intracellular JEV particle production. The study demonstrated that the CW-33 derivative with a bromo substitution at the C-2 anilino ring improved the antiviral activity JEV, providing the structure-antiviral activity relationship for the development of anti-JEV agents.